2017
DOI: 10.1101/162255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetically EngineeredMedeaGene Drive System in the Worldwide Crop Pest,D. suzukii

Abstract: Synthetic gene drive systems possess enormous potential to replace, alter, or suppress wild populations of significant disease vectors and crop pests; however, their utility in diverse populations remains to be demonstrated. Here, we report the creation of the first-ever synthetic Medea gene drive element in a major worldwide crop pest, D. suzukii. We demonstrate that this drive element, based on an engineered maternal "toxin" coupled with a linked embryonic "antidote," is capable of biasing Mendelian inherita… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In Aedes aegypti, several regulatory elements able to drive gene expression in a tissue-and temporal-specific manner have been identified through extensive study (Akbari et al 2013a) and transgenesis (Coates et al 1999;Kokoza et al 2000;Moreira et al 2000;Smith et al 2007). Future functional characterization of uncharacterized genes and regulatory elements may lead to the development of innovative genetic population control technologies such as precision guided sterile males (Kandul et al 2019b), and gene drive systems (Akbari et al 2013b(Akbari et al , 2014aChamper et al 2016;Buchman et al 2018bBuchman et al , 2018aKandul et al 2019aKandul et al , 2019bLi et al 2019) which can be linked to anti-pathogen effectors (Buchman et al , 2019b potentially providing paradigm-shifting technologies to control this worldwide human disease vector. Overall, our results provide a comprehensive snapshot of gene expression dynamics in the development of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In Aedes aegypti, several regulatory elements able to drive gene expression in a tissue-and temporal-specific manner have been identified through extensive study (Akbari et al 2013a) and transgenesis (Coates et al 1999;Kokoza et al 2000;Moreira et al 2000;Smith et al 2007). Future functional characterization of uncharacterized genes and regulatory elements may lead to the development of innovative genetic population control technologies such as precision guided sterile males (Kandul et al 2019b), and gene drive systems (Akbari et al 2013b(Akbari et al , 2014aChamper et al 2016;Buchman et al 2018bBuchman et al , 2018aKandul et al 2019aKandul et al , 2019bLi et al 2019) which can be linked to anti-pathogen effectors (Buchman et al , 2019b potentially providing paradigm-shifting technologies to control this worldwide human disease vector. Overall, our results provide a comprehensive snapshot of gene expression dynamics in the development of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In a highly influential paper, Chen et al showed that the Medea dynamics observed in natural systems, in which non- Medea offspring of Medea mothers are unviable, could be replicated synthetically through the action of a maternally expressed toxin linked to a zygotically expressed antidote . The antidote consists of a recoded version of the target gene that is immune to the effect of the toxin and is expressed zygotically in embryos that inherit the Medea element. ,, This potent toxin–antidote combination confers a selective advantage to the Medea -containing allele relative to the wildtype allele, enabling it to spread into a population from very low initial frequencies (Figure C). Medea constructs engineered thus far function through the action of RNA interference-based toxin–antidote combinations in which synthetic miRNA toxins are expressed during oogenesis in Medea -bearing females, disrupting an essential embryonic gene in all progeny; however these have been difficult to engineer in some species, and it is hoped that CRISPR gene editing will accelerate the development of maternal toxins in the near future …”
Section: Threshold-independent Drive Systemsmentioning
confidence: 99%
“…In a highly influential paper, Chen et al showed that the Medea dynamics observed in natural systems (26), in which non-Medea offspring of Medea mothers are unviable, could be replicated synthetically through the action of a maternally-expressed toxin linked to a zygotically-expressed antidote (10). The antidote consists of a recoded version of the target gene that is immune to the effect of the toxin, and is expressed zygotically in embryos that inherit the Medea element (9,10,27). This potent toxin-antidote combination confers a selective advantage to the Medea construct, enabling it to spread into a population from very low initial frequencies ( Figure 1C).…”
Section: Threshold-independent Drive Systemsmentioning
confidence: 99%
“…It should be noted that, for both drive and remediation to be effective, the toxin and antidote must be highly efficient. A naturally-occurring allele conferring resistance to the maternal toxin will be favored as drive is occurring, and in fact this was observed in a Medea element recently synthetically engineered in D. suzukii (27).…”
Section: Threshold-independent Drive Systemsmentioning
confidence: 99%